what is the formula of
(a-b)3 ?
Answers
Answered by
1
Step-by-step explanation:
its my pleasure to help you.
please mark me as a brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d86/31c83472a40446d25794550656483e56.jpg)
Answered by
10
◆ (a - b)³ = a³ -b³ - 3ab (a -b)
More formulas:-
- (a +b)³ = a³ + b³ +3ab (a + b)
- (a + b)² = a² + b² + 2ab
- (a - b)² = a² + b² - 2ab
- (a + b) (a - b) = a² - b²
- (a + b + c)² = a² + b² + c² + 2ab + 2bc +2ac.
- a³ - b³ = (a - b) ( a² + ab + b²)
- a³ + b³ = (a + b) ( a² - ab + b²)
- (a + b + c )³ = a³ +b³ + c³ +3abc
Similar questions